Creative Process : Documentary Filmmaking - Jacobs, Michael; Tronson, Tyler; Tronson, Alex (My University, 2013)
From the arts to the sciences, and everywhere in between, the connections and interactions that define a liberal arts university were explored, and to make a case for the interdisciplinary nature of education by highlighting the processes of learning and working that is commonly shared. The purpose of this study was to produce a short documentary film exploring the role of the creative process through a diverse array of disciplinary perspectives and educational activities at the University of Wisconsin--Eau Claire.
Color poster with text, photographs, and diagrams.
Keywords: Creative process; University of Wisconsin--Eau Claire--Interdisciplinary education; Posters